Cross-cultural differences in children's concepts of health and illness Diferenças transculturais nos conceitos de saúde e doença de crianças - Evely Boruchovitch; Birgitte R. Mednick (Universidade de São Paulo, 1997)
INTRODUCTION: In spite of general agreement that cross-cultural research is needed in the health area, most existing investigations of children's development of health and illness-related concepts have involved samples from developed countries. The study examined the development of the concepts of health and illness as a function of subject's age, socio-economic status (SES), gender and grade level in a Brazilian sample of 96 elementary and junior high school students. METHODS: Subjects were interviewed individually and their ideas of health and illness were assessed through open-ended questions. Participants' answers were transcribed verbatim and subjected to content analysis. RESULTS: Chi-square analyses revealed significant age, school grade and SES-related differences in participants' concepts of health and illness. DISCUSSION AND CONCLUSION: The themes employed by subjects to define both health and illness were broadly consistent with those found by previous research. The study showed a predictable relationship between subject's age and school grade level and increasingly more highly differentiated and multidimensional concepts of health and illness. This investigation suggests that, for the most part, cross-cultural similarities in children's concepts of health and illness may be more striking than the differences. INTRODUÇÃO: Apesar de diversas pesquisas indicarem a necessidade de investigações transculturais na área de saúde, a maioria dos estudos existentes sobre o desenvolvimento de conceitos de saúde e doença em crianças e adultos foram realizados com amostras de países desenvolvidos. Assim, foi realizada uma pesquisa com o objetivo de investigar o impacto das variáveis idade, série escolar, nível socioeconômico e sexo na formação dos conceitos de saúde e doença em escolares brasileiros de primeiro grau. MÉTODO: Os sujeitos foram entrevistados individualmente, num total de 96, e suas idéias sobre saúde e doença foram medidas por questões abertas. Suas respostas foram transcritas na íntegra e estudadas por análise de conteúdo. RESULTADOS: Provas de Chi-quadrado revelaram diferenças significativas nos conceitos de saúde e doença dos participantes em relação à idade, série escolar e nível socioeconômico. DISCUSSÃO E CONCLUSÃO: Os temas empregados pela amostra para definir saúde e doença foram consistentes com os encontrados nas pesquisas provenientes de outros países. Na medida em que a idade e a série escolar aumentam, os conceitos de saúde e doença tornam-se mais diferenciados e multidimensionais. As semelhanças entre culturas na conceituação de saúde e doença mostraram-se muito mais intrigantes do que as diferenças.